Contemporary and emerging issues in trade theory and policy - Marjit, Sugata, 1959-; Yu, Eden Siu-hung (Frontiers of economics and globalization ;, 2008)
This is a new volume in the Frontiers in Economics & Globalization series. This book deals with a wide-range of trade and development issues in terms of well-known general equilibrium structure. This volume shows how neo-classical models of trade theory can be used to highlight many challenging contemporary global problems. This book is a new volume in the Frontiers in Economics & Globalization series. It deals with a wide-range of trade and development issues. It focuses on neo-classical models of trade theory to highlight the challenges of global trade problems.